Conventional CD11chigh Dendritic Cells Are Important for T Cell Priming during the Initial Phase of Plasmodium yoelii Infection, but Are Dispensable at Later Time Points - Ueffing, Kristina; Abberger, Hanna; Westendorf, Astrid M.; Matuschewski, Kai; Buer, Jan; Hansen, Wiebke (Frontiers in Immunology, 2017)
Dendritic cells (DCs) are highly specialized antigen-presenting cells that orchestrate adaptive immune responses to pathogens. During malaria infection pro- and anti-inflammatory T cell responses have to be tightly balanced to ensure parasite clearance without induction of severe immune pathologies. However, the precise role of CD11chigh DCs in this process is still discussed controversially. Here, we demonstrate that long-term depletion of conventional CD11chigh DCs in Plasmodium yoelii (P. yoelii)-infected diphtheria toxin (DT)-treated RosaiDTR/CD11c-cre mice interferes with the activation of CD8+ and CD4+ T cells as well as CD4+Foxp3+ regulatory T cells at early time points during infection. Moreover, systemic levels of the pro-inflammatory cytokines IFN-g and TNF-a were decreased in P. yoelii-infected mice deficient for CD11chigh DCs compared to infected RosaiDTR controls. To further elucidate the importance of CD11chigh DCs during the later phase of infection, we treated RosaiDTR/CD11c-cre and control mice with DT only from day four of P. yoelii infection onwards. Strikingly, this approach had no impact on the activation and IFN-g production of CD4+ and CD8+ effector T cells. These results indicate that CD11chigh DCs play a crucial role in eliciting effector T cell responses during the initial phase, but are dispensable during ongoing infection with P. yoelii.